Evaluation of adult immunoglobulin A vasculitis with oxidative stress and inflammation biomarkers - Zeynep Busra Balik; Ahmet Rifat Balik; Ahmet Omma; Cigdem Yucel; Murat Kizilgun; Esra Firat Oguz; Salim Neselioglu; Ozcan Erel (Medicine Science, 2023)
IgA vasculitis (IgAV) is a leukocytoclastic vasculitis affecting small vessels and is more common in children than in adults. In this study, we aimed to investigate the effects of oxidative stress in adult IgAV patients by Dynamic Thiol Disulfide Homeostasis (DTDH) and Ischemia Modified Albumin (IMA) levels. We also aimed to correlate the presence of inflammation detected by C-Reactive Protein (CRP) and Highly Sensitive C-Reactive Protein (hsCRP) with these oxidative stress parameters. Forty-one IgAV patients and forty-five controls were included in the study. Patients were classified as "active" or "in remission" according to the British Vasculitis Activity Score (BVAS). Measured parameters were compared between the groups. DTDH, IMA, CRP and hsCRP parameters were analyzed in both patient and control groups. According to our results, disulfide (p=0.047), index 1 (p [Med-Science 2023; 12(3.000): 758-63]